Due north [videorecording (DVD)] - Stam, Joseph; Alford, David; McVey, Rick; Lanier, Sharonne; Smallbone, Libby (BMG-Global, 2026)
After his third arrest, 21-year-old Jason avoids prison with house arrest at a remote ranch with a grandfather he's never met. As family secrets surface and violent men from their past close in, the two must unite or lose everything.